Management of the Cavity After Removal of Giant Cell Tumor of the Bone - Wang, Yushan; Tian, Qiaoqiao; Wu, Chenyang; Li, Haoze; Li, Jian; Feng, Yi (Frontiers in Surgery, 2021)
PURPOSE: To find out the most appropriate management scheme through the analysis and comparison of different inactivation methods and filling materials METHOD: A systematic literature search was performed using the terms, anhydrous ethanol, phenol, hypertonic saline, cryotherapy, thermal therapy, bone reconstruction, GCTB and etc. Selected articles were studied and summarized. The mechanism, clinical effects, and influence on bone repair of various methods are presented. Recent developments and perspectives are also demonstrated. RECENT FINDINGS: Compared to curettage alone, management of the residual cavity can effectively reduce the recurrence of giant cell tumours of bone. It is a complex and multidisciplinary process that includes three steps: local control, cavity filling and osteogenic induction. In terms of local control, High-speed burring can enlarge the area of curettage but may cause the spread and planting of tumour tissues. Among the inactivation methods, Anhydrous ethanol and hyperthermia therapy are relatively safe and efficient. The combination of the two may achieve a better inactivation effect. When inactivating the cavity, we need to adjust the approach according to the invasion of the tumour. Filling materials and bone repair should also be considered in management.